Sistem Informasi Monitoring Perkuliahan Pada Sekolah Tinggi Ilmu Kesehatan (STIKES) Bali - Budiarthana, I Wayan; Budayasa, I Putu Gede; Willdahlia, Ayu Gede (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2019)
The Bali Institute of Health Sciences (STIKES) is a higher education institution in the health sector. Education in an institution needs to be monitored especially the lecture process. At present, the process of monitoring lectures is carried out by recording into paper documents. Several problems arise, namely at the end of each semester staff who perform lecture attendance recapitulation must open a sheet per lecturer attendance form sheet. Then from the lecturer attendance form, the staff in charge must type back into the Microsoft Excel application. This resulted in 2 problems, namely the occurrence of delays in reporting and the difficulty of monitoring lectures by Puket I. From these problems a system is needed that is able to provide information on the presence of lecturers and is able to present information on lecture activities in realtime. The design of this system is translated through Data Flow Diagrams and built using PHP language, for display using CSS, and database using MySQL. Testing this system uses blackbox testing. The lecture monitoring information system can display information about the implementation of lectures for Chairperson I Assistant in real time and can facilitate STIKES Bali staff in conducting lecturers' attendance.